THE EVOLUTION OF MEDICALTERMINOLOGY IN UZBEK MEDIADISCOURSE - Akbarkhodjaeva Feruza Abduganiyevna (Western European Studies, 2025)
This narrative explores the development of medical terminology within Uzbek media discourse, applying hermeneutic principles to post-editing of machine-generated texts. It draws on interdisciplinary research – from translation studies, media linguistics, and hermeneutics – to understand how translators and post-editors interpret semantically layered medical terms within cultural and communicative contexts. Key literature includes works by local Uzbek scholars (e.g., Turaeva, 2023; Karimova, 2023), as well as international contributions from The Lingua Spectrum (Kasperė et al., 2024; Iskandarova, 2022). The study examines specific case examples, such as translation of “chronic obstructive pulmonary disease” and culturally resonant terms like “immunity,” illustrating how hermeneutics aids in preserving precision, pragmatics, and ethical sensitivity. Findings underscore the potential of hermeneutically informed post-editing to enhance terminological accuracy in a way that respects both medical standards and audience comprehension. Recommendations point toward integrating hermeneutic training into post-editor education, and considering AI-supported frameworks for transparent, context-aware translation workflows.
Keywords: media discourse; medical terminology; hermeneutics